Masturina’s Transcription Services: an undergraduate project / Masturina Khairulazam and Mohammad Nor Afandi Ibrahim - Khairulazam, Masturina; Ibrahim, Mohammad Nor Afandi (Akademi Pengajian Bahasa, 2021)
This paper reports on a diploma-level final year project on transcription services offered by an online start-up company, Masturina’s Transcription Services. Its core business is transcribing academic material both in English and Malay at an affordable rate for undergraduates in local universities. Identifying potential clients and negotiating the charges and turnaround time of services are conducted through various social platforms such as WhatsApp, Telegram, and e-mail. Once clients are satisfied with the terms of service, then only payment would be made. Within a period of seven weeks, 11 transcription services were performed for six student clients of various field of studies which led to an income of RM183.80. The results indicated that a high satisfactory outcome of Masturina’s Transcription Services in terms of its qualities and turn-around time has helped students cope with their online studies during the COVID-19 pandemic and eventually given significant impact on their academic academic performance. Among areas to be looked into would be more transcriptions on study-related terms and higher service charges.